CHEMICAL CHARACTERIZATION BY GC-MS FROM THE AERIAL PARTS OF FAGONIA LONGISPINA (ZYGOPHYLLACEAE) - N, HAMIDI; L, ZIANE; M, DJELLOULI; HA, LAZOUNI (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective was to characterize the phytochemical constituents in ethyl acetate (EtOAc) extract from the aerial parts of Fagonia longispina (zygophyllaceae) by gas chromatography-mass spectrometry (GC-MS). Methods: The dried powder of the aerial parts of F. lonjispina was extracted exhaustively with ethanol. The extract was concentrated, diluted with water and partitioned with EtOAc. The residue of the EtOAc extract was performed using a GC-MS. Results: Chemical constituents of the EtOAc extract of F. Longispina Family (Zygophylaceae) were identified by GC-MS and their relative concentrations were determined. F. Longispina extract contained 12 compounds: Cis-4-(4 -T-butylcyclohexyl)-4-methyl-2-pentanone (33.33%), 4beta-(tert-butyl)1alpha-(1methylvinyl) cyclohexanem ethanol (09.52%), cyclohexyl-2-methylene butanyl ketone (14.28%), trans-4-(â€“t-butylcyclohexyl)-4-methyl2-pentanone (9.52%), 2,6,10-trimetyl, 14-Ethylne-14 pentadecene (6.66%), 2-decen-1-ol (cas) (4.76%), 3,7,11,15-tetramethyl-2-hexadecen-1-ol (2.85%), 2-nonen-1-ol (4.76%), citronellyl acetate (2.85%), tetratetracontane (3.38%), hexatriacontane (cas) (3.38%), and phytolacetate (4.76%). ’ Conclusions: This GC-MS study helps to predict the formula and structure of phytoconstituents which can be used as drugs, and further investigation may leads to the development of drug formulation. These compounds are probably the major players in the antioxidant responses evoked by the plant. Keywords: Etyl acetate extract, Gas chromatography-mass spectrometry analysis, Fagonia longispina.